2021
DOI: 10.1128/spectrum.01273-21
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for the Analysis of Bacterial Membrane Vesicles: Methods of Vesicle Production and Quantification Can Influence Biological and Experimental Outcomes

Abstract: Recent years have seen a surge in interest in the roles of BMVs in host-microbe interactions and interbacterial communication. As a result of such rapid growth in the field, there is a lack of uniformity in BMV enumeration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 68 publications
1
54
0
Order By: Relevance
“…In addition, we did not observe TLR9 activation in response to stimulation with B. fragilis OMVs at any MOI examined in this study, which suggests that the amount of DNA delivered by B. fragilis OMVs may not have been sufficient to mediate TLR9 activation (35). We have previously shown that BMVs produced by different strains of a bacterial species vary in their amount of DNA and RNA cargo and therefore differ in their ability to activate their respective TLRs (35). Therefore, although we did not see activation of TLR8 and TLR9 by B. fragilis OMVs in our study, we cannot exclude the possibility that stimulation of these cells with an increased amount of OMVs, or with OMVs produced by a different B. fragilis strain that harbor a greater concentration of DNA and RNA, may activate these TLRs.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…In addition, we did not observe TLR9 activation in response to stimulation with B. fragilis OMVs at any MOI examined in this study, which suggests that the amount of DNA delivered by B. fragilis OMVs may not have been sufficient to mediate TLR9 activation (35). We have previously shown that BMVs produced by different strains of a bacterial species vary in their amount of DNA and RNA cargo and therefore differ in their ability to activate their respective TLRs (35). Therefore, although we did not see activation of TLR8 and TLR9 by B. fragilis OMVs in our study, we cannot exclude the possibility that stimulation of these cells with an increased amount of OMVs, or with OMVs produced by a different B. fragilis strain that harbor a greater concentration of DNA and RNA, may activate these TLRs.…”
Section: Discussionmentioning
confidence: 53%
“…B. fragilis OMVs were purified by OptiPrep (60% iodixanol(v/v); Sigma-Aldrich, USA) density gradient ultracentrifugation as previously described ( 6 , 12 , 35 , 36 ). In brief, OMV samples were adjusted to 45% (v/v) OptiPrep in 2ml DPBS and were then overlaid with a discontinuous OptiPrep gradient containing 2ml each of 40%, 35%, 30%, 25% and 20% OptiPrep (v/v) in DPBS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, we found that the averaged diameter of 103 + -EVs (130 nm) is slightly bigger than 103 − -EVs (105 nm) ( Figure 1 ). The size of EVs in Gram-positive bacterial varies between different bacterial strains [ 34 , 35 , 36 , 37 ], throughout various stages of bacterial growth [ 38 ], and environmental conditions [ 27 , 39 , 40 ]. As the reports that the size distribution of EVs of the invasive Streptococcus pyogenes strains SSI-1 were 1.31 times bigger than the non-invasive Streptococcus pyogenes strains JRS4 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%